Short-time work compensation schemes and employment - Pierre Cahuc (IZA World of Labor, 2019)
Government schemes that compensate workers for the loss of income while they are on short hours (known as short-time work compensation schemes) make it easier for employers to temporarily reduce hours worked so that labor is better matched to output requirements. Because the employers do not lay off these staff, the schemes help to maintain permanent employment levels during recessions. However, they can create inefficiency in the labor market, and might limit labor market access for freelancers and those looking to work part-time.
Keywords: E24; J22; J65; 330; working time; unemployment insurance; labor hoarding; short-time work; unemployment; employment